2017
DOI: 10.11648/j.edu.20170602.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sun Safety Education Program for High School Students in Beijing, China

Abstract: Actions in reducing excessive sun exposure during childhood and adolescence has been a goal of a series of programs. The objective of this study was to evaluate a multi-component high school-based intervention program to increase sun safety knowledge and sun protection behaviors among students in Beijing, China. Volunteers from three high schools in Beijing were randomized to three groups. Group A was given a 2-year intervention program consisting of multi-unit presentations plus a series of educational materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The geographical regions where the intervention was delivered were globally diverse; three studies each in Australia [ 12 , 15 , 23 ] and Iran [ 14 , 16 , 17 ], two in the United States [ 22 , 24 ], and one each in Brazil [ 14 ], China [ 20 ], Denmark [ 18 ], Spain [ 25 ], and Turkey [ 21 ]. Of the 13 studies, seven reported that they were based on a theoretical framework which included Protection Motivation Theory [ 13 , 17 ], the PRECEDE model [ 16 ], the Health Belief Model [ 22 ], the Theory of Planned Behaviour [ 23 ], the Extended Parallel Process Model [ 24 ], or some combination of behavioural frameworks [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The geographical regions where the intervention was delivered were globally diverse; three studies each in Australia [ 12 , 15 , 23 ] and Iran [ 14 , 16 , 17 ], two in the United States [ 22 , 24 ], and one each in Brazil [ 14 ], China [ 20 ], Denmark [ 18 ], Spain [ 25 ], and Turkey [ 21 ]. Of the 13 studies, seven reported that they were based on a theoretical framework which included Protection Motivation Theory [ 13 , 17 ], the PRECEDE model [ 16 ], the Health Belief Model [ 22 ], the Theory of Planned Behaviour [ 23 ], the Extended Parallel Process Model [ 24 ], or some combination of behavioural frameworks [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the12 studies where duration of the intervention was provided, five were single sessions of less than one-hour duration [ 14 , 19 , 21 , 22 , 24 ]. The remaining interventions were longer with six reporting multiple sessions, usually over a block of time [ 12 , 13 , 18 , 23 ] with one exception where two lessons were delivered each year for three years [ 20 ]. The intervention where shade was provided was long-term [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Lai, using one control group and two intervention groups (A and B), where group A who were given a 2 years-long intervention program consisting of multi-unit presentations plus a series of educational materials resulted a more significant improvement than group B who were given one year-long education materials only. In addition, both groups also demonstrated positive improvement in subjects' behaviour after intervention, although with different degrees of improvement [12].…”
Section: The Application Of Safety Education In Grade 4 Of Primary Scmentioning
confidence: 87%